2021
DOI: 10.1097/rli.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Assessment of Swine Renal Fibrosis Using Quantitative Magnetization Transfer Imaging

Abstract: Objectives: Quantitative magnetization transfer (qMT) is useful for measurement of murine renal fibrosis at high and ultrahigh field strengths. However, its utility at clinical field strengths and in human-like kidneys remains unknown. We tested the hypothesis that qMT would successfully detect fibrosis in swine kidneys with unilateral renal artery stenosis (RAS) at 3.0 T. Methods: The qMT protocol is composed of MT scans with variable flip angles and offset frequencies, and of B 0 , B 1 , and T 1 mapping. Pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
1
1
Order By: Relevance
“…To the best of our knowledge, this is the first study evaluating the reproducibility of MTI in ischemic kidneys as well as between 1.5T and 3T field strengths. Previous studies have demonstrated the feasibility of MTI in kidneys at 3T [19,[27][28][29]. In the present study, MTI showed good reproducibility at 3T, but we observed significant differences over time in the MTR values in the normal kidney cortex and medulla at 600 Hz and in the STK medulla at both 600 Hz and 1000 Hz.…”
Section: Discussioncontrasting
confidence: 42%
“…To the best of our knowledge, this is the first study evaluating the reproducibility of MTI in ischemic kidneys as well as between 1.5T and 3T field strengths. Previous studies have demonstrated the feasibility of MTI in kidneys at 3T [19,[27][28][29]. In the present study, MTI showed good reproducibility at 3T, but we observed significant differences over time in the MTR values in the normal kidney cortex and medulla at 600 Hz and in the STK medulla at both 600 Hz and 1000 Hz.…”
Section: Discussioncontrasting
confidence: 42%
“…The relaxation and semi-solid pool parameters were set based on previous studies on CEST and magnetization transfer contrast. [28][29][30][31] The parameters include: semi-solid pool concentration (𝑀 " $ ) = 1,554 mM, CEST concentration (𝑀 % $ ) = 50 mM, B0 field = 11.7 T (500 MHz), kba = 20 s -1 , kca = 500 -6,500 s -1 , T1a = 2 sec, T1b = 1 sec, T1c = 1 sec, T2a = 60 msec, T2b = 10 µsec, T2c =100 msec. We employed a 1 msec timestep for optimizing the 100 msec pulses (100 steps per 100 msec pulse) and a delay between of 1 to 100 msec between the pulses with a total of 2000 total steps for this pre-saturation pulse train including the pulses and delays.…”
Section: Optimization Parametersmentioning
confidence: 99%